Perfil dos proprietários de cavalos Crioulos no Brasil - Oyarzabal, Carolina da Rosa (2023)
Equine breeding is part of the diverse range of sectors that composse the agribusiness, and appears in increasing development due to the large number of professionals involved and, consequently, the generation of many direct and indirect jobs. The aim of this project is to characterize the main actor that drives equine breeding, the breeder and owner of horses, specifically of the Criollo breed. The breed is present throughout the national territory, and the expansion of the Criollo horse chain has brought together many breeders, service providers, investors and admirers over the 90 years of establishment of the Brazilian Association of Criollo Horse Breeders (ABCCC). It is thus necessary to map, to characterize, and know what is the current profile of the Criollo breeder. The survey was carried out through a from, containing 26 questions, applied to active and regular members of ABCCC, available on the association's website for a period of 60 days. A total of 771 responses were obtained, which corresponds to 18,5% of the total sample of members. Data tabulation and analysis were descriptive, using graphs, figures and tables to present the results. It could be observed that currently those who breed and invest in Criollo horses, see in the activity, in addition to passion and personal satisfaction, the opportunities for entrepreneurship and good business. This mapping is essential for the development of other research that makes up the expansion of the production chain of the Criollo horse, an activity that moves and heats up agribusiness.